Marine Eco-Climatological Conditions Captured in the West Waters of North Sumatra - Nababan, Bastian Vepry Odynata; Samiaji, Joko; Elizal, Elizal (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2024)
Fishery resources in Indonesia, especially in the waters of the Western part of North Sumatra, are closely related to the oceanographic dynamics. Knowledge is needed about the conditions of Marine Eco-Climatology in fishing areas rich in fishery resources. This research was conducted in January-April 2021 at the Sibolga Archipelago Fisheries Port, Sibolga Fisheries and Marine Resources Supervisory Post, and College of Fisheries and Marine Science in Pandan Central Tapanuli. The research method was a survey method with a simple regression statistical test. Based on the results of this study, it was slowed that the air temperature in Sibolga City from 2010-2019 ranged between 23-28⁰C and was categorized as normal. The rainfall in Sibolga City in 2010-2019 ranged from 100-600 mm per month, and the wind speed value was 6-12 knots. The effect of these parameters on the catch showed a weak status. It was known that the best time to carry out the fishing is at average temperatures of 24-27⁰C, rainfall less than 3000 m3 /day, and wind speeds of 6-8 knots